Delivery of Dietary and Lifestyle Interventions in Pregnancy: is it Time to Promote the Use of Electronic and Mobile Health Technologies? - O'Brien, Cecelia M.; Cramp, Courtney; Dodd, Jodie M. (Seminars in Reproductive Medicine, 2016)
Fifty percent of women who enter pregnancy are overweight or obese, increasing complications for both the mother and the infant, along with significant burden on individuals and the health care system. Pregnancy represents a “teachable moment” in a woman's life, however, antenatal interventions focusing on improving dietary and physical activity patterns have been associated with modest behavior change. There are many barriers that need to be overcome, including lack of knowledge, access and time pressures. Advancing mobile and electronic health technologies may represent an adjunct tool to support traditional face-to-face consultations and facilitate behavior change, but further rigorous evaluation of the technologies and their impact on health outcomes is required. Well-designed antenatal intervention trials with particular attention to the structure and method of information provision are required to further assess the feasibility of such technology.
Keywords: obesity; pregnancy; antenatal intervention; mobile technology; E-health